Overview Of Fraudulent Behaviour At PT. Advantage SCM - Aisyah Wulandari Marbun; Jordi Satria Fernando (Journal of Accounting and Auditing, 2025)
Abstract Purpose – Aims to obtain evidence regarding the effect of the whistleblowing system and financial pressure on fraud with good corporate governance as a moderating variable.Design/methodology/approach – This research uses a quantitative type, this research was conducted using a questionnaire distributed to employees of PT Advantage SCM, namely 250 questionnaires distributed via social media. Each questionnaire contains 49 questions for respondents to answer. From the distribution of respondents, 190 respondents answered. To get the results of this study, researchers used SmartPLS version 3.0. Findings – The results of this study found that the whistleblowing system has a negative effect on fraud and is not significant, financial pressure has a positive and insignificant effect on fraud, good corporate governance strengthens the whistleblowing system against fraud and good corporate governance strengthens financial pressure against fraud. Research limitations/implications – The limitation in this study is the response of the respondents, some employees who have been contacted are difficult to take the time to fill out the questionnaire within the specified time period.